Transparência na gestão pública municipal: uma avaliação dos municípios do estado do Piauí - Silva, Maria Jéssica da (2024)
Transparency has been one of the most common issues on the global stage in which governments are recommended to practice responsible practices and provide information about their actions. This is a tool that must be applied to all governments in Brazil and, therefore, in the state of Piauí it should be no different. Therefore, the purpose of this study is to analyze whether the municipalities of Piauí, with more than 10 thousand inhabitants, are complying with the provisions of the Access to Information Law regarding the dissemination of mandatory information through the global computer network (internet), as well as identifying whether the municipalities of Piauí present their information in an accurate and safe way for society to know about their acts in government decisions and actions, verifying the degree of public transparency by managers through the dimensions of the Municipal Public Management Transparency Index – ITGP- M. The research is characterized as documentary with information analysis, through descriptive statistics, in which electronic spreadsheets were used to collect data and Rstudio to process the data with a descriptive approach and quantitative classification. In view of this, through the ITGP-M it was found that the municipalities in question are partially disclosing their data and failing to comply with some items set out by the LAI in the dissemination of mandatory information via the global computer network (internet). Encouragement and publicity for the population's participation are scarce and social interaction is not being achieved. Furthermore, municipalities with data deficiencies and one of the websites were inactive or outdated. That said, even though the majority of municipalities in Piauí, with more than 10 thousand inhabitants, are within the average, these results are below expectations, verifying the need for data updates and the provision of a more effective transparency portal. Among these measures, it is suggested to transform their websites into open access media with relevant content, with updated data for the population.